RICHARD WAGNER’S OPERAS IN 21ST CENTURY BALTICS: THE SAME WAGNER OR ANOTHER? - Lauma Mellena-Bartkevica (European Scientific Journal, ESJ, 2014)
Celebrating the anniversary 200 of Richard Wagner, also the opera theaters of the Baltic States have paid the tribute to the great German composer and thinker by staging several operas, and even a full „Ring” cycle at the Latvian National Opera. Apart from the anniversary, the question of how the ideas of Wagner are interpreted nowadays arises, starting from his concept of the total work of art (Gesamstkunstwerk) and ending up with the stage director as the new author, who recreates the story in a postmodern way, adding new contexts and interpretations to the initial ideas. The paper will analyze particularly the “Ring” cycle in Riga performed fully after a 100 years break, questioning the existing stereotypes related to Wagner’s music and personality that impede to be open for new interpretations and the complex semantic density created by the stage directors. The main aspects will concern the general problematics of the contemporary productions of so called “classical” operas in terms of representation and reception, the postmodern approach to the opera direction, mostly represented by combination of the mythical and archetypical structures of Wagner’s original works with the contexts and references to the modernity and the history of the 20th century, thus re-creating the Wagner’s story in new dimensions to be perceived by the modern opera goer able to uncover different layers of the meanings depending on his knowledge and experience. Also the question of why Wagner is/might be topical nowadays will be discussed.